Transforming Medical Assessment: Virtual OSCEs in Community Medicine - Medical Students' Standpoints" - Palve, Sachin Bhaskar; Palve, Suchitra Sachin (Indian Journal of Community Health, 2025)
Background: Virtual OSCE sessions offer significant utility as an educational tool by enhancing accessibility standardization, immediate feedback, and technology integration. Aim & Objective: To study the utility of a Virtual OSCE assessment method and to determine the students' standpoints and attitude of this approach in comparison to the traditional structured viva method. Settings and Design: A cross-sectional study was conducted among 150 first-year medical undergraduates at a medical institute. Methods and Material: OSCE stations assessed blood pressure and nutritional Anaemia. Students were sensitized in small groups via a virtual platform. Clinical skills station was evaluated virtually, while other stations were assessed physically. A structured, self-administered validated questionnaire with close and open-ended responses were used to analyze students' standpoints on the virtual OSCE. Statistical analysis: The Shapiro–Wilk test of normality, Wilcoxon–Mann–Whitney test, and the Phi or mean square contingency coefficient were applied. Results: Out of 150 students, 133 participated in the assessment. Among them, 82.4% found virtual OSCE teaching engaging, 80.4% found it interactive, and 87.6% felt it enhanced their interrogation and interpersonal skills. Most students not only appreciated the virtual OSCE for being interesting, innovative, and less time-consuming but also found it to be an effective tool for reducing their fear of facing teachers through immediate feedback. However, a few still preferred the traditional viva method for in-person contact. Conclusions: Virtual OSCEs are a feasible, engaging, and interactive alternative to in-person assessments, enhancing confidence, history-taking, and communication skills.